The Extreme-ultraviolet Precursors and Postcursors of Solar Flares - Larisza D. Krista (The Astrophysical Journal)
EUV brightenings are small-scale magnetic reconnection events that consistently appear before and after solar flares. However, it is not well understood how EUV precursors might foreshadow flares and what the physical connection is between the EUV signatures and flares. We studied flare-active and inactive periods in three separate studies using the Detection and EUV Flare Tracking (DEFT) tool. In Study 1, EUV signatures were identified in 200 no-flare days, in Study 2 EUV signatures before 360 flares were analyzed, and in Study 3 close to 36,000 EUV signatures were detected, and their pre- and postflare distribution and trends were studied. Our key questions were as follows: do EUV signatures occur consistently before flares, do EUV signatures occur without flares, are there flares without EUV precursors, and is it possible to forecast different magnitude flares based on preceding EUV signature trends? Study 1 showed that in no-flare periods EUV signatures were only detected 4% of the time. Study 2 showed that EUV precursors were present 92% of the time within 6 hr before ≥C-class flares. Study 3 showed that over 90% of the signatures were associated with flares (≥B class), and over 50% of all signatures were associated with ≥M-class flares. A superposed epoch analysis showed precursor frequency peaks at  ∼70 and 100 minutes before M- and X-class flares, respectively, while B- and C-class flares had no notable precursor frequency peaks. These results demonstrate the close connection between EUV signatures and flares and the significant potential EUV signatures have in improving space weather forecasting.